Ni(I)–Alkyl Complexes Bearing Phenanthroline Ligands: Experimental Evidence for CO2 Insertion at Ni(I) Centers - Somerville, Rosie J; Odena, Carlota; Obst, Marc F; Hazari, Nilay; Hopmann, Kathrin H; Martin, Ruben (Journal of the American Chemical Society, 2020)
Although the catalytic carboxylation of unactivated alkyl electrophiles has reached remarkable levels of sophistication, the intermediacy of (phenanthroline)Ni(I)–alkyl speciescomplexes proposed in numerous Ni-catalyzed reductive cross-coupling reactionshas been subject to speculation. Herein we report the synthesis of such elusive (phenanthroline)Ni(I) species and their reactivity with CO2, allowing us to address a long-standing question related to Ni-catalyzed carboxylation reactions.